2021
DOI: 10.5435/jaaos-d-21-00073
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Formal Patient Complaints and Malpractice Events Involving Hand and Upper Extremity Surgeons

Abstract: Introduction: Our purpose was to define and categorize patient complaints within a hand surgery practice over a 10-year period. In addition, we aimed to define surgeon and patient factors associated with formal complaints. Methods: All patients who filed a complaint with our institution's patient advocacy service against six hand surgeons in an academic practice over a 10-year period were recorded and categorized using the Patient Complaint Analysis Sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 15 publications
1
14
0
Order By: Relevance
“…This compares to a 0.20% complaint rate among hand and upper extremity surgeons and a 0.15% complaint rate among pediatric orthopedic surgeons, which have been previously reported by our group. 6,8 These data are consistent with results from Dambrino et al, 9 who demonstrated that spine neurosurgeons had an increased risk of complaints compared with other physicians. Our overall malpractice event rate among the six surgeons was found to be 0.23%.…”
Section: E523supporting
confidence: 86%
See 4 more Smart Citations
“…This compares to a 0.20% complaint rate among hand and upper extremity surgeons and a 0.15% complaint rate among pediatric orthopedic surgeons, which have been previously reported by our group. 6,8 These data are consistent with results from Dambrino et al, 9 who demonstrated that spine neurosurgeons had an increased risk of complaints compared with other physicians. Our overall malpractice event rate among the six surgeons was found to be 0.23%.…”
Section: E523supporting
confidence: 86%
“…Interestingly, while prior series have shown the association between patient demographics (obesity, tobacco use, and worker’s compensation) and surgical complications, these were not associated with complaints in our series or prior similar studies of other orthopedic subspecialties. 6,8,16–18…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations